Analisis Pemahaman Peraturan Permainan Bola Voli di Akademi Bola Voli UMBY - Rofiul Amrew; Febri Sulistya (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This research is based on the fact that there are still many athletes at the Volleyball Academy, Mercu Buana University, Yogyakarta who do not understand the rules of volleyball. This study aims to determine the level of understanding of volleyball rules in athletes of the Volleyball academy of Mercu Muana University Yogyakarta. This research is a quantitative descriptive research. The research method used is a survey and data collection technique using a questionnaire or questionnaire. The population taken was all female athletes of the Mercu Buana University Volleyball Academy Yogyakarta totaling 20 athletes. The sampling technique in this study is a total sampling technique. The instrument used is a questionnaire using 30 questions. Furthermore, the validity test uses a percentage formula. The data analysis technique uses descriptive analysis which is expressed in the form of percentages. Based on the results of the study, the average results of the 8 factors presented are in the low category.